Expression of RND efflux pumps mediated antibiotic resistance in Pseudomonas aeruginosa clinical strains. (April 2021) - Zahedi bialvaei, Abed; Rahbar, Mohammad; Hamidi-Farahani, Ramin; Asgari, Ali; Esmailkhani, Aylin; Mardani dashti, Yasaman; Soleiman-Meigooni, Saeed
Abstract: Resistance-Nodulation-Division (RND) efflux pumps are responsible for multidrug resistance in Pseudomonas aeruginosa . The present study aimed to evaluate the overexpression of RND efflux pumps and its role in the antibiotic resistance of P. aeruginosa clinical isolates. A number of 122 isolates were obtained from three military hospitals in Tehran, Iran. In order to determine the antibiotic resistance, the isolates were identified and assessed by the disk diffusion and agar dilution methods. This study investigated the gene expression of four multi-drug efflux pump systems (MexAB-OprM, MexCD-OprJ, MexEF-OprN and MexXY (-OprA)) and its correlation with antibiotic resistance. The isolates indicated that the highest resistance rate was against ticarcillin (80%), followed by ciprofloxacin (74%) and meropenem (71%). Most of them expressed mexB (69%), mexC (28.7%), mexE (43.4%), and mexY (74.6%), suggesting that mexB and mexY were highly expressed in the studied strains. The overexpression of mexB and mexY was significantly more prevalent in the ICU wards (p = 0.033). Furthermore, there was a significant correlation between the expression of RND-type efflux pumps and the resistance to most anti-pseudomonal antibiotics. Highlights: Pseudomonas aeruginosa, is a Gram-negative bacterium and causes hard-to-treat infections. RND efflux pumps are responsible for multidrug resistance in P.aeruginosa. The isolates showed the highest resistance rate against ticarcillin, followed by ciprofloxacin and meropenem. Most of isolates expressed mexB (69%), mexC (28.7%), mexE (43.4%) and mexY (74.6%). There is a significant correlation between the expression of efflux pumps and the resistance to antibiotics.